TINJAUAN YURIDIS PENETAPAN NOMOR 29/PDT.P/2019 PN GIANYAR TERHADAP UNDANG-UNDANG NOMOR 16 TAHUN 2019 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DAN PUTUSAN MAHKAMAH AGUNG REG NOMOR 1400K/PDT/1986 - Sugi Kurnia Pakpahan; Mardalena Hanifah; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Interfaith marriage is a marriage bond between a man and a woman who embracedifferent religions and beliefs while maintaining their respective beliefs. The phenomenon ofinterfaith marriage is not new in Indonesia. Previously, there were rows of Indonesianwomen who married non-Muslim men. A well-known case is the marriage of Andy VonnyGani P, a Muslim couple. The purpose of this writing: First, to find out the arrangements formarriage according to Law Number 1 of 1974 concerning marriage. Second, to find out theregulation of interfaith marriage according to law in Indonesia in relation to the SupremeCourt Decision Number 1400k/pdt/1986 (Case Study of Determination Number 20/pdt.p/2019PN Gianyar)The type of research in this paper is normative legal research. Normative legalresearch is legal research conducted by examining legal literature or secondary data. Thisresearch focuses on research on legal systematics. Research on legal systematics can becarried out on certain laws or recorded laws.From the results of the research, there are two main things that can be concluded.First, the provisions for marriage of different religions are not regulated in the MarriageLaw, Article 2 Paragraph (1) of the Marriage Law is a